PENGARUH JENIS PACKING PADA MENARA PACKED-BED ABSORBER DALAM PENYERAPAN GAS NOx - Kadarjono, Agoeng; Yusnitha, Erilia; Santosa, Agus Sartono Dwi; Winastri, Pertiwi Diah (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
THE EFFECT OF PACKING TYPE ON THE PACKED-BED ABSORBER IN ABSORPTION OF NOx. Design of NOx effluent gas processing needs to be done for broth preparation and gel casting activities in the UO2 kernel fabrication process series. The availability of this effluent processing tool will increase the economic value and process efficiency, reduce the amount of the chemicals needed, and minimize the hazards associated with toxicity and contamination. The design of the effluent processing tool chose the packed-bed absorber using NOx gas as a feed stream and water as an absorbent medium. The packed-bed absorber has been designed and calculated to determine the effect of various types of packing (pall, ralu, and nor-pac ring) for the absorbtion of the NOx gas. To determine the effect of the packing type, it is carried out by simulating fluid flow rate on diameter, effective surface area of packing, pressure drop, mass transfer coefficient, packing column height, and tower height by inserting into the appropriate equations using the EXCEL program. The inclusion of the effect of feed flow rate and type of packing in the calculation resulted in smaller diameter for the tower containing pall ring packing than the diameter of tower containing other fillings but gave higher pressure drop values, effective surface area of packing, total mass transfer coefficient, and tower height. Increase in NOx gas absorption causes an increase in the amount of packing space and tower height. Increase in operating pressure and temperature causes a decrease in packing and tower height, whereas increase in flooding factor, beside causing a decrease in packing and tower height, decreases the tower diameter. This type of pall ring packing is a design choice because it produces small/economic dimensions.